Business Risk and Sales Growth on Financial Performance in Defense Industry Companies in Indonesia - Wulan Fitri Utami; Posma Sariguna Johnson Kennedy; Muliahadi Tumanggor (CV. Rayyan Dwi Bharata, 2023)
An independent and strong defense industry can support the development of defense forces and the economy. Where in reviewing its development can be seen through its financial aspects or the company's financial performance. Assessment of financial performance can be seen from the level of profit or profitability that has been achieved by the company in carrying out its operational activities. The purpose of this study was to determine the effect of business risk and sales growth on the financial performance of defense industry companies in Indonesia for the 2011-2020 period. This research is a quantitative research with a sample focused on 5 defense industry companies which are members of DEFEND ID. The analysis used is multiple linear regression. The results showed that partially business risk has an effect on financial performance while sales growth has no effect on financial performance. Meanwhile, business risk and sales growth simultaneously affect the company's performance, with a coefficient of determination of 89.4%.